Accurate printing of a zirconia molar crown bridge using three-part auxiliary supports and ceramic mask projection stereolithography. Issue 15 (15th October 2019) - Lian, Qin; Wu, Xiangquan; Li, Dichen; He, Xiaoning; Meng, Jiali; Liu, Xiaodong; Jin, Zhongmin
Abstract: Zirconia ceramic is a widely used material for dental restoration. Stabilized zirconia all-ceramic teeth have excellent mechanical properties, biocompatibility, and aesthetic properties. At present, the CAD/CAM technique for zirconia all-ceramic dental prosthesis leads to low material efficiency and high tool wear. Although restorations fabricated using additive manufacturing are gaining attention, it is still very challenging to obtain accurate shapes and proper mechanical properties in zirconia restorations. In this investigation, a type of three-part auxiliary support was adopted and added to the occlusal surface to fabricate a typical molar crown bridge. A ceramic solid content of 40 vol% acrylic-based slurry was prepared, and a molar crown bridge was fabricated using mask projection stereolithography. The experimental results showed that the average dimensional error of the printed green body was ±150 μm. The density of the sintered ceramic parts was 6.026 g/cm 3, and the three-point bending strength was 541 ± 160 MPa, which is higher than that of human dentin (160 MPa), but lower than that of CAD/CAM zirconia (900–1200 MPa). Although the proposed process still needs to be optimized to improve the mechanical properties and reliability of the crown bridge, the mask projection process combined with the adopted three-part auxiliary supports are capable of individualized manufacturing of complex zirconia crown bridges.